Combined hepatocellular and cholangiocarcinoma with sarcomatous transformation - Paisarn Boonsakan (2018)
Combined hepatocellular and cholangiocarcinoma with sarcomatous transformation was first recognized in Ramathibodi Hospital in 2005. This variant of carcinoma has been increasingly reported particularly from Asian countries. Dedifferentiation of the epithelial component to various sarcomatous components is likely the underlying mechanism. The causative factors of hepatocarcinogenesis in Thailand include chronic viral hepatitis B or C, exposures to aflatoxin B1 and nitrosamine(s) and occasionally some certain nodular hepatocellular lesions due to arterial hyperperfusion. It is suggested that the recent change of the Thai peoples' life style to an increased consumption of fast foods containing food preservatives especially nitrate or nitrite, the nitrosamine precursor, may allow heavy exposure(s) to the chemical carcinogen(s) i.e. nitrosamine(s) leading to sarcomatous transformation of the carcinoma.